E-learning Acceptance: The Mediating Role of Student Computer Competency in the Relationship Between the Instructor and the Educational Content - Sharif-Nia, Hamid; Allen, Kelly-Ann; Arslan, Gokmen; Reardon, Jonathan; She, Long *; Ghahrani, Nassim; Rahmatpour, Pardis; Fomani, Fatemeh Khoshnavay (Elsevier, 2024)
Drawing on the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), this online cross-sectional study explored the mediating role of computer competencies in the relationship between the instructors’ role and the course's educational content with e-learning acceptance among 403 nursing students in Iran. Based on the results, e-learning acceptance was predicted by students’ computer competency (β=.18, p<.001). Computer competency mediated the association between the instructor's role and course content with e-learning acceptance.